The changing golden ratio for aesthetics in dentistry - Edanur Keleş (Conservative Dentistry Journal, 2026)
Background: The golden ratio (ϕ≈1.618) has long been associated with beauty and balance in art and human anatomy. In dentistry, particularly in smile design, mathematical proportions like the golden ratio have been proposed as objective tools for evaluating dental aesthetics. Purpose: This study aims to investigate the contemporary relevance and clinical applicability of the golden ratio in aesthetic dentistry, examining its integration into smile design and its relationship with perceived attractiveness. Methods: A total of 60 subjects (30 males, 30 females) with natural dentition were evaluated. Standardized frontal photographs were analyzed using digital software to measure the visible width ratios of the maxillary anterior teeth (central incisors, lateral incisors, and canines), which were then compared with the golden ratio (1.618). One-sample t-tests and Pearson correlation were used for statistical analysis. Results: The mean lateral–central incisor ratio was 0.67±0.05, and the mean canine–lateral incisor ratio was 0.63±0.06. Overall deviations from the golden ratio were statistically significant (p<0.05). No strong correlation was found between the exact golden ratio and subjective aesthetic ratings (r=0.28,p>0.05). Conclusion: The golden ratio offers a useful conceptual framework for dental aesthetics but should not be considered an absolute criterion. Aesthetic evaluation in dentistry must balance objective mathematical analysis with individualized clinical judgment and patient-specific harmony.